Plasmodium berghei-Released Factor, PbTIP, Modulates the Host Innate Immune Responses - Kalia, Inderjeet; Anand, Rajesh; Quadiri, Afshana; Bhattacharya, Shreya; Sahoo, Bijayalaxmi; Singh, Agam Prasad (Frontiers in Immunology, 2021)
The Plasmodium parasite has to cross various immunological barriers for successful infection. Parasites have evolved mechanisms to evade host immune responses, which hugely contributes to the successful infection and transmission by parasites. One way in which a parasite evades immune surveillance is by expressing molecular mimics of the host molecules in order to manipulate the host responses. In this study, we report a Plasmodium berghei hypothetical protein, PbTIP (PbANKA_124360.0), which is a Plasmodium homolog of the human T-cell immunomodulatory protein (TIP). The latter possesses immunomodulatory activities and suppressed the host immune responses in a mouse acute graft-versus-host disease (GvHD) model. The Plasmodium berghei protein, PbTIP, is expressed on the merozoite surface and exported to the host erythrocyte surface upon infection. It is shed in the blood circulation by the activity of an uncharacterized membrane protease(s). The shed PbTIP could be detected in the host serum during infection. Our results demonstrate that the shed PbTIP exhibits binding on the surface of macrophages and reduces their inflammatory cytokine response while upregulating the anti-inflammatory cytokines such as TGF-β and IL-10. Such manipulated immune responses are observed in the later stage of malaria infection. PbTIP induced Th2-type gene transcript changes in macrophages, hinting toward its potential to regulate the host immune responses against the parasite. Therefore, this study highlights the role of a Plasmodium-released protein, PbTIP, in immune evasion using macrophages, which may represent the critical strategy of the parasite to successfully survive and thrive in its host. This study also indicates the human malaria parasite TIP as a potential diagnostic molecule that could be exploited in lateral flow-based immunochromatographic tests for malaria disease diagnosis.